Reasons for Winning Hearts in the Noble Qur’an - an Explanatory Study - - Aziz , Aya (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the master of all creation, Muhammad (may Allah bless him and grant him peace), and his family and his faithful companions. This research came in order to shed light upon what has been mentioned in the Holy Qur’an of clear and clear verses that indicated by their content matters .By complying with them, a person earns the love of people, and this love reflects on the society’s stability. So I proceeded to shed light on it, and clarify its meaning, and its role in winning hearts and spreading love. Among these causes there are major cause that is considered a necessity of faith, and some of them are subsidiary ones that stem from the main causes that are no less important than the first causes in achieving love between people. Each of them plays a major role in maintaining the cohesion of society and strengthening the bonds of brotherhood. Among them, and in this context, I will mention what could be mentioned from the verses in which there are a number of matters that are considered as reasons to win people's hearts.